Synthesis of N-(5-(Substitutedphenyl)-4,5-dihydro-1H-pyrazol-3-yl)-4H-1,2,4-triazol-4-amine from 4-Amino-4H-1,2,4-triazole - Ashvin D. Panchal; Pravin M. Patel (E-Journal of Chemistry, 2011)
N-(4H-1,2,4-Triazol-4-yl)acetamide (2) were prepared by reaction of 4-amino-4H-1,2,4-triazole (1) with acetyl chloride in dry benzene. It has been reacted with various aromatic aldehyde to afford 3-(substitutedphenyl)-N-(4H-1,2,4-triazol-4-yl)acrylamide (3a-e). The synthesis of N-(5-substitutedphenyl)-4,5-dihydro-1H-pyrazol-3-yl)-4H-1,2,4-triazol-4-amine (4a-e) is achieved by the cyclisation of 3a-e with hydrazine hydrate in ethanol. The structures of synthesized compounds were characterized by 1H NMR and IR spectroscopic studies. The purity of the compounds was checked by thin layer chromatography.